Influence of process parameters on the extraction of flavanones from mandarin peel - Makovšek, Katja (Acta chimica slovenica, 2012)
Flavanones are an important group of flavonoids that are characteristic for citrus. In the present work isolation of flavanones from mandarin peel was performed by conventional extraction using water, ethanol, acetone and aqueoussolutions of acetone and ethanol. The extracts were analysed on the content and composition of flavanones. Furthermore the DPPH radical scavengingactivity of extracts was determined. Finally, the influence of extraction parameters (particle size, extraction temperature, extraction time,material to solvent ratio, number of extraction stages and type of solvent) on the yield and the efficiency of extraction were determined by Plackett-Burman experimental design. The results showed that 70% aqueous solution of acetone was the most efficient solvent for isolation of flavanonesfrom mandarin peel. The main flavanones present in the obtained extracts were hesperidin (HES) and narirutin (NRT). The number of extraction stages influenced the yield of extraction, type of solvent influenced the hesperidin extraction efficiency and particle size of material influenced the narirutin extraction efficiency.
Keywords: conventional extraction; flavanone; hesperidin; mandarin peel; narirutin; Plackett-Bauman experimental design